Pendampingan Usaha dengan Memanfaatkan Pemasaran Berbasis Digital untuk UMKM di Desa Biluango Kabupaten Bone Bolango: Business Assistance by Utilizing Digital-Based Marketing for Small and Medium Enterprises in Biluango Village, Bone Bolango District - Arsyad, Nur Fadilah; Koniyo, Nursela; Koyansow , Noviyanti; Radjak , Nurain (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
After the COVID-19 pandemic, MSMEs must be able to rise to improve their family's economic conditions. This is done by exploring the potential of the village and taking advantage of technological advances. This service was carried out in Biluango Village, Bone Bolango Regency. Biluango Village has MSMEs, especially those engaged in the culinary sector. This service activity aims to assist MSME Goroho Mama Azam regarding production and digital marketing. The method of implementing the service is divided into four stages, including 1) MSME Survey Stage, 2) Production assistance, 3) Marketing digitalization assistance, and 4) Monitoring and evaluation. The results are: 1) Partner products become more diverse, 2) Product appearance becomes more attractive, 3) Wider market reach by utilizing social media, and 4) Partners become proficient in using social media in carrying out business transactions.